MAVLONO GADOIYS LIFE AND HIS LITERARY LEGACY (International journal of artificial intelligence, 2024)
The information dealing with the life and his literary activity can be found in memorials of Alisher Navoi (1441-1501), the great classical poet and founder of Uzbek language and literature. There were not any other riliabce notes done by men of literary activity concerning the life of the poet, e[cept Navoiy’s works. We can say that Mavlono Gadoiy’s life and his literary legacy has been taken as the subject of discussion since the beginning of XX century.